Make Way for Traditions: Echoes of Auslegungsgeschichte in Retellings of Genesis 1-3 in Select Jewish, Catholic, and Protestant Children's Bibles, 1980-2020 - Wilkowski, Rachel Kathryn (Trinity College Dublin. School of Religion. Discipline of Religions and Theology, 2025)
When Bible stories are retold in children's Bibles, the authors and illustrators of these works are inevitably influenced by their own understandings of and interactions with interpretive tradition. These interpretive influences do not necessarily act consciously on children's Bible authors and illustrators; however, both conscious and unconscious interpretations are embedded in the text and image of the children's Bibles. As such, children's Bibles function as valuable material objects in reception historical research and are simultaneously influenced by prior receptions of the biblical text in question. To this point, much children's Bible research has focused on the effect of socio-cultural influences on the reception of Bible in children's Bibles; however, this study examines the effect of reception historical influences, in the form of so-called 'professional' biblical interpretation (i.e., Auslegungsgeschichte), on the manner in which the Bible is received in children's Bibles. This study focuses, in particular, on the reception of Genesis 1-3 in select Protestant, Catholic, and Jewish children's Bibles published between 1980 and 2020. Cross-confessional analysis of the interpretive perspectives embedded in the text and image of the children's Bibles is engaged in order to determine, first, whether the interpretation(s) in the children's Bibles are present and persistent within their tradition's history of reception and, second, whether there are certain interpretive distinctives across the three traditions. This study focuses on eight themes distributed across five chapters. The second chapter focuses on two themes related to science and creation: the depiction of the manner in which God created the cosmos (Gen 1:1-3) and the portrayal of the six creation days (Genesis 1). The third chapter considers two themes related to what it means to be human: creation in the imago Dei (Gen 1:26-27) and relationship between humans and the created order (Gen 1:28 and 2:15). The fourth chapter considers a single theme 'the relationship between male and female' from three vantage points: the differing narratives of human creation in Genesis 1 and 2; male and female roles, both pre- and postlapsarian; and the relative culpability of male and female in the events of Genesis 3. The fifth chapter analyzes two themes related to the emergence of evil: the depiction of the Eden serpent in Genesis 3 and the manner in which the problem with and consequences of eating from the forbidden Tree are described. The sixth chapter then considers the characterization of God in the first three chapters of Genesis, with attention to attributes, emotions, and roles that are applied to him. This analysis determines that, on the whole, the interpretations embedded in the children's Bibles tend to have precedent within their tradition. What becomes conspicuous throughout this analysis, however, is that Protestant children's Bibles are more dissimilar to the Masoretic text of Genesis 1-3 than their Catholic and Jewish counterparts. This is indicative of greater interpretive shaping of the biblical text in Protestant children's Bibles. This study concludes by considering why this might be the case in light of the overall approaches to biblical interpretation in Protestant, Catholic, and Jewish traditions.
APPROVED
Keywords: Reception History; Children's Bibles; Genesis 1-3